Multimode ultrasound viscoelastography for three-dimensional interrogation of microscale mechanical properties in heterogeneous biomaterials. (September 2018) - Hong, Xiaowei; Annamalai, Ramkumar T.; Kemerer, Tyler S.; Deng, Cheri X.; Stegemann, Jan P.
Abstract: Both static and time-dependent mechanical factors can have a profound impact on cell and tissue function, but it is challenging to measure the mechanical properties of soft materials at the scale which cells sense. Multimode ultrasound viscoelastography (MUVE) uses focused ultrasound pulses to both generate and image deformations within soft hydrogels non-invasively, at sub-millimeter resolution, and in 3D. The deformation and strain over time data are used to extract quantitative parameters that describe both the elastic and viscoelastic properties of the material. MUVE was used in creep mode to characterize the viscoelastic properties of 3D agarose, collagen, and fibrin hydrogels. Quantitative comparisons were made by extracting characteristic viscoelastic parameters using Burger's lumped parameter constitutive model. Spatial resolution of the MUVE technique was found to be approximately 200 μm, while detection sensitivity, defined as the capability to differentiate between materials based on mechanical property differences, was approximately 0.2 kPa using agarose hydrogels. MUVE was superior to nanoindentation and shear rheometry in generating consistent microscale measurements of viscoelastic behavior in soft materials. These results demonstrate that MUVE is a rapid, quantitative, and accurate method to measure the viscoelastic mechanical properties of soft 3D hydrogels at the microscale, and is a promising technique to study the development of native and engineered tissues over time.